Trust in Corporate Image and Its Impact on Customers' Loyalty - Mochamad Miswanto Gunawan; Tutik Tutik; Krisnawati Setyaningrum Nugraheni; Ray Octafian (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
Customer loyalty plays an important role in Industrial production and service. This banking industry is an industry based on the principle of trust (agent of trust), so it is necessary to create an image first so that prospective customers grow trust in our company first. The phenomenon that occurs in the field today seems to be starting to show a decline in customers due to several current economic conditions, customers who often use credit are starting to decline but prefer to switch to savings products even though the credit process is easy and fast, competing with commercial banks. Research objectives (1) to analyze the effect of corporate ability image and corporate social responsibility image on trust; (2) Analyzing the influence of corporate ability image and corporate social responsibility image on loyalty; (3) Analyzing the influence of corporate ability image and corporate social responsibility image on loyalty through trust; (4) Analyzing the effect of trust on loyalty. The research method is descriptive quantitative method. The sampling method used in this study is Accidental Sampling, which is a sampling technique carried out by appointing anyone or by chance provided that they have used a product from a BPR. Corporate ability image has a positive and significant impact on customer trust. Corporate Social Responsibility Image has a positive and significant influence on customer trust. Corporate Ability Image affects customer loyalty through trust. Corporate Social Responsibility Image affects customer loyalty through trust affects customer loyalty. Trust has a significant influence on customer loyalty.